The Role of Sports Law in Enhancing Educational Outcomes: Cross-Cultural Analysis - Yanoor Maqsood; Gevan Naufal Wala (Siber Nusantara Review, 2025)
Sports law plays a crucial role in shaping educational outcomes by providing a regulatory framework that governs sports activities within educational institutions. This study examines the role of sports law in enhancing educational outcomes through a cross-cultural analysis between Indonesia and India, two populous nations with diverse educational systems. Using a qualitative comparative approach, this research analyzes legal frameworks, policy implementations, and their impacts on student development in both countries. Data were collected through document analysis, in-depth interviews with education and sports stakeholders, and observation of implementation practices. The findings reveal that both countries have established comprehensive sports law frameworks, though they differ significantly in implementation approaches and cultural contexts. Indonesia's National Sports System Law emphasizes integration of sports into the national education curriculum, while India's National Sports Development Code focuses on talent identification and development programs. Both frameworks demonstrate positive impacts on student participation, academic achievement, and character development. However, challenges persist in both systems, including resource allocation, infrastructure limitations, and coordination among stakeholders. Best practices from both countries suggest that effective sports law implementation requires strong policy support, adequate funding, trained personnel, and community engagement. This study contributes to the understanding of how sports law can be optimized to improve educational outcomes across different cultural contexts.